Crude protein and lactose on performance, intestinal morphology and expression of genes related to intestinal integrity and immune system of piglets - Valente Júnior, Dante Teixeira (2020)
The present study was carried out to evaluate the effects of crude protein (CP) and lactose (LAC) levels on performance, intestinal morphology and gene expression associated to epithelial integrity and activation of the immune system of piglets. A total of 120 commercial castrated male and female hybrid piglets, weaned at 21 days of age and 7.88 ± 0.9 kg initial body weight, were assigned to a randomized block design, in a 2 × 3 factorial arrangement, with 2 levels of crude protein (CP, 20.0 and 24.0%) and 3 levels of lactose (LAC, 8.0, 12.0 and 16.0%), with 10 replicates and two piglets per experimental unit. There was no interaction (P > 0.05) between CP and LAC levels for any performance variables and serum urea nitrogen concentration (SUN). Piglets fed diets with 24.0% CP had higher average daily feed intake (ADFI; P = 0.048) compared to those fed 20.0% CP. Diets containing 12.0 or 16.0% LAC resulted in higher (P < 0,01) ADFI and average daily gain (ADG) of piglets compared to the 8.0% LAC diet. Pigs fed 12.0% LAC diets had greater (P = 0.018) final body weight (final BW) than those fed 8.0 and 16.0% LAC diets. There was no effect (P = 0.164) of LAC concentration on feed:gain ratio (F:G). Piglets consuming 20.0% CP diets had lower (P < 0.001) SUN than piglets fed 24.0% CP diets. Regardless of diet CP levels, piglets fed 12.0 or 16.0% LAC diets had higher duodenum and ileum villous height (P = 0.02 and P = 0.006, respectively). Interactions (P < 0.05) were observed between CP and LAC for duodenum, jejunum and ileum crypt depth. Piglets fed 24.0% CP diet with 12.0 or 16.0% LAC had lower duodenum crypt depth, and piglets fed 24.0% CP diet with 12.0 LAC had lower ileum crypt depth than those fed with 8.0% LAC. There were interactions (P < 0.05) between the CP and LAC for duodenum and ileum villus height:crypt depth ratio. Piglets fed 24.0% CP diet with 12.0 or 16.0% LAC had higher duodenum and ileum villus height:crypt depth ratio compared to those fed 24.0% CP with 8.0% LAC. Interactions (P < 0.05) were observed between CP and LAC levels for gene expression of IL-6 and TNFα. However, there was no effect of LAC on the expression of these cytokines in the diets with 20.0 or 24.0% CP. Similarly, there was a tendency for interaction (P = 0.07) between CP and LAC in the IL-1β gene expression. Whilst, at the levels of 20.0 and 24.0% CP there was no effect of LAC on the expression of IL-1β. There was interaction (P = 0.025) between CP and LAC for haptoglobin (Hp) gene expression. At 24.0% CP piglets fed 16.0% LAC had lower expression of Hp. Gene expression of TGF β1 and occludin were not influenced (P > 0.05) by CP and LAC levels of the diets. There was interaction (P = 0.012) between CP and LAC in gene expression of the ZO-1, and the diet with 16.0% LAC was more efficient in decreasing gene expression of ZO-1 compared to 8.0 and 12.0% LAC. In conclusion, concentration of 12.0% LAC in the diet improves performance of piglets from 21 to 35 days old regardless of diet CP content. The inclusion of 12.0 and 16.0% LAC in the diet promotes improvements in intestinal morphology, being more evident in the diet with 24.0% CP compared to 20.0% CP. In addition, increasing inclusion of LAC in the diet with higher level of CP (24.0%) decreases the immune system activation and reduces the permeability of the intestinal epithelium. Keywords: Immune system. Intestinal morphology. Lactose. Piglets. Prebiotic. Weaning.